Fetal tissue transplantation: can it be morally insulated from abortion?. Issue 2 (June 1991) - Strong, C
Abstract : Ethical controversy over transplantation of human fetal tissue has arisen because the source of tissue is induced abortions. Opposition to such transplants has been based on various arguments, including the following: rightful informed consent cannot be obtained for use of fetal tissue from induced abortions, and fetal tissue transplantation might result in an increase in the number of abortions. These arguments were not accepted by the National Institutes of Health (NIH) Human Fetal Tissue Transplantation Research Panel. The majority opinion of the panel stated that abortion and fetal tissue use are entirely separate issues, and that tissue use is ethically acceptable because it can be morally insulated from the issue of abortion. In support of this view, panel members and others have replied to the arguments put forward by opponents of fetal tissue use. However, replies to the two arguments mentioned above have been unsatisfactory, and the shortcomings of those replies are identified herein. Examination of the arguments pro and con suggests that fetal tissue use cannot be completely insulated from the issue of abortion. Thus, in seeking an ethical justification for fetal tissue transplantation we must consider reasons other than those put forward by the NIH panel. In this paper it is argued that whatever wrong is involved in using fetal tissue from induced abortions must be balanced against the benefits for patients, and it is on this basis that fetal tissue transplantation can be ethically justified.